Perancangan Fasilitas Penyimpanan dan Pembelajaran Kreativitas untuk Anak Usia Dini - Meinasari Ardelia; Adi Santosa; Grace Setiati Kattu (Intra, 2019)
Aged 3 to 5 years is golden age for children. At these phases they will learn to write, read, and explore their living environment. Beside physical, children will develop in terms of their psychomotor, cognitive, affective and creativity aspects. Furniture is one of the most important needs to support learning and playing activities. Meanwhile, there are many parents who facilitate their children to learn, play, and store items with less appropriate furniture for children, they are furniture for adults. Furniture for children and adults are different, both in terms of design, color, and size. Therefore, furniture for children with the right design, color and size is needed.